2003
DOI: 10.1074/jbc.m208741200
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement for Polyamines for Intestinal Epithelial Cell Migration Is Mediated through Rac1

Abstract: The rapid migration of intestinal epithelial cells is important to the healing of mucosal ulcers and wounds. This cell migration requires the presence of polyamines and the activation of RhoA. RhoA activity, however, is not sufficient for migration because polyamine depletion inhibited the migration of IEC-6 cells expressing constitutively active RhoA. The current study examines the role of Rac1 and Cdc42 in cell migration and whether their activities are polyamine-dependent. Polyamine depletion with ␣-difluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 39 publications
5
72
0
Order By: Relevance
“…The expression of a DN-Rac mutant decreased cadherin-mediated cell-cell contacts in both primary keratinocytes and MDCKII cells [Hirano et al, 1992;Jou and Nelson, 1998]. We previously found that polyamine depletion decreased Rac1 activity [Ray et al, 2003], and the expression of CA-MEK1 restored Rac1 activity, migration and the ACS in these cells [Vaidya et al, 2005]. EGF also increased the activities of MEK1 and Rac1 and migration (Figs.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The expression of a DN-Rac mutant decreased cadherin-mediated cell-cell contacts in both primary keratinocytes and MDCKII cells [Hirano et al, 1992;Jou and Nelson, 1998]. We previously found that polyamine depletion decreased Rac1 activity [Ray et al, 2003], and the expression of CA-MEK1 restored Rac1 activity, migration and the ACS in these cells [Vaidya et al, 2005]. EGF also increased the activities of MEK1 and Rac1 and migration (Figs.…”
Section: Discussionmentioning
confidence: 83%
“…6). Since Rac1 activates RhoA and Cdc42 in these cells [Ray et al, 2003], these results suggest that Rho GTPases regulate adherens junctions and the ACS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations